2013
DOI: 10.1371/journal.pone.0080556
|View full text |Cite|
|
Sign up to set email alerts
|

Pain and Pessimism: Dairy Calves Exhibit Negative Judgement Bias following Hot-Iron Disbudding

Abstract: Pain is defined as an unpleasant sensory and emotional experience associated with actual or potential tissue damage, but emotional states are difficult to directly assess in animals. Researchers have assessed pain using behavioural and physiological measures, but these approaches are limited to understanding the arousal rather than valence of the emotional experience. Cognitive bias tasks show that depressed humans judge ambiguous events negatively and this technique has been applied to assess emotional states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 31 publications
6
96
3
2
Order By: Relevance
“…Negative emotional states also appear to influence judgment abilities in dairy calves. Very young Holstein calves exhibited a negative judgment bias for at least 22 hrs after hot-iron disbudding; the calves were less likely to approach ambiguous screen colors in two sessions after the procedure (Neave, Daros, Costa, von Keyserlingk, & Weary, 2013). A second cognitive bias study investigated 13 mother-reared Holstein dairy calves' abilities to discriminate between red and white colors on a computer monitor.…”
Section: Emotionsmentioning
confidence: 99%
“…Negative emotional states also appear to influence judgment abilities in dairy calves. Very young Holstein calves exhibited a negative judgment bias for at least 22 hrs after hot-iron disbudding; the calves were less likely to approach ambiguous screen colors in two sessions after the procedure (Neave, Daros, Costa, von Keyserlingk, & Weary, 2013). A second cognitive bias study investigated 13 mother-reared Holstein dairy calves' abilities to discriminate between red and white colors on a computer monitor.…”
Section: Emotionsmentioning
confidence: 99%
“…For example, restraint in isolation (Doyle et al, 2010), unpredictable environments and shearing (Sanger et al, 2011) in sheep, disbudding in cattle (Neave et al, 2013) and unpredictable environments in rats (Harding et al, 2004) all result in shifts in the expectation of a positive (i.e. optimistic) or negative (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, if the animal does not respond or the latency to respond is similar to that of the negative cue/location then the response is considered as being pessimistic. This type of test has been used to assess judgement bias in livestock including sheep (Doyle et al, 2010;Sanger et al, 2011;Destrez et al, 2012), pigs (Douglas et al, 2012), cattle (Neave et al, 2013) and poultry (Salmeto et al, 2011;Wichman et al, 2012) and most such tests are sensitive enough to detect differences attributed to the affective state of the animals. However, it has been argued that this type of task, where the only outcome measured is the latency to approach or not approach within a time limit, has limitations in its interpretation as negative affective states may be associated with a general reduction in activity and feeding motivation reflecting a response bias rather than a judgement bias (Brilot et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They found that when a tone was played with a frequency close to or equal to 4 kHz, rats housed in unstable conditions were slower to press the lever than rats housed in stable conditions, which is consistent with a decreased anticipation of reward. This "pessimistic" judgment bias has since been demonstrated in a few other species (including humans) and situations (Brilot et al, 2010;Daros et al, 2014;Hales et al, 2014;Mendl et al, 2009;Neave et al, 2013;Papciak et al, 2013;Scheele et al, 2013;Verbeek et al, 2014). Conversely, Swan and Hickman (2014) …”
Section: Resultsmentioning
confidence: 94%